PRODUCTIVITY OF DURUM SPRING WHEAT VARIETIES ACCORDING TO ANCESTORS - A. S. Usov (Зерновое хозяйство России)
During the years 2013-2014 the laboratory of plant-breeding of Institute of Plant-Growing named after V.Ya. Yuriev carried out researches in a long-term (42 years) nine fallow-grain-plowing crop rotation sequences with the following rotation of cultures: ‘black’ fallow – winter wheat – sweet beetroot – spring wheat – peas – winter wheat – maize for grain, soybean – spring wheat – sunflower. The article presents the study results of response of durum spring wheat varieties on yield formation depending on precipitations and daily average temperatures growing in a long-term crop rotation. It has been determined that it’s necessary to plant durum spring wheat after maize for grain and soybean to get high yields and after sweet beetroot to level the negative conditions of the year. The vegetation period of the year 2014 was more favourable for high yields of durum spring wheat (3.55–5.70 t/ha), but in the dry conditions with high temperatures of the year 2013, the productivity of the crop (depending on the variety and ancestor) was 0.86-2.00 t/ha because of.